The role of endogenous and exogenous triggers in the development of acne - Mariya V. Kail-Goryachkina (LLC "MEDIAFORMAT", 2023)
The paper presents current data on the impact of endogenous and exogenous triggers on the clinical manifestations of acne. The major triggers are discussed in detail. The importance of genetic factors for the development of dermatosis is reported. The role of hormonal factor, hyperandrogenism, in the pathogenesis of the disease is displayed. The data on the adverse effects of stress on the course of acne are provided. The association of the diet with the acne exacerbation/onset is exposed. The negative role of smoking in triggering the non-inflammatory type acne is reported.